Genome-wide identification of quantitative trait loci for important plant and flower traits in petunia using a high-density linkage map and an interspecific recombinant inbred population derived from Petunia integrifolia and P. axillaris - Zhe Cao; Yufang Guo; Qian Yang; Yanhong He; Mohammed I. Fetouh; Ryan M. Warner; Zhanao Deng (Horticulture Research, 2019)
Petunia: Enhancing commercial cultivars Uncovering the genetics behind desirable traits in petunia plants could help improve commercial cultivars. While petunia plants are a key feature of the global horticultural industry, the limited genetic variability in commercial plants makes it difficult to improve desired plant traits. Zhanao Deng at the University of Florida, US, and co-workers conducted a genome-wide QTL identification study using a crossbred population combining two petunia  species, P. integrifolia and P. axillaris. The team phenotyped the petunias in an open-air sub-tropical field rather than in an artificial environment like previous studies. They identified and characterized 17 genetic loci for seven important aesthetic traits, ranging from flower count to plant size. The petunia species had very different genetic backgrounds, likely stemming from their different geographic origins. The two species each can contribute novel genes for enhancing cultivated petunia cultivars.